2012
DOI: 10.1121/1.4718454
|View full text |Cite
|
Sign up to set email alerts
|

The effects of noise-bandwidth, noise-fringe duration, and temporal signal location on the binaural masking-level difference

Abstract: The effects of forward and backward noise fringes on binaural signal detectability were investigated. Masked thresholds for a 12-ms, 250-Hz, sinusoidal signal masked by Gaussian noise, centered at 250 Hz, with bandwidths from 3 to 201 Hz, were obtained in N(0)S(0) and N(0)S(π) configurations. The signal was (a) temporally centered in a 12-ms noise burst (no fringe), (b) presented at the start of a 600-ms noise burst (backward fringe), or (c) temporally centered in a 600-ms noise burst (forward-plus-backward fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 73 publications
(115 reference statements)
0
16
0
Order By: Relevance
“…Traditionally, psychometric functions for N 0 S 0 and N 0 S π are treated as being parallel (e.g., Egan et al, 1969; Yasin and Henning, 2012). That is, the size of the BMLD does not depend on the accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, psychometric functions for N 0 S 0 and N 0 S π are treated as being parallel (e.g., Egan et al, 1969; Yasin and Henning, 2012). That is, the size of the BMLD does not depend on the accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Townsend and Altieri (2012) have developed a new capacity metric A(t) which takes into account correct and incorrect trials. This capacity measure will be extremely valuable to determine if these results generalize to SNRs more commonly used in the binaural masking literature, where psychometric functions are measured between chance detection and near-perfect accuracy (Egan et al, 1969; Yasin and Henning, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The BMLD decreases as the bandwidth increases. Recently, Yasin & Henning () published data on the effect of masker gating on the BMLD in a band‐widening type of experiment, which seem to be at odds with the previous results. The BMLDs of their forward‐backward fringe condition are shown in the left panel of Fig.…”
Section: Band‐widening Experimentsmentioning
confidence: 99%
“…Recently, Verhey & Yasin () showed that overall signal duration and ramp duration had a substantial effect on the size of the BMLD for a narrowband noise masker centred at the signal frequency whereas these stimulus parameters hardly affected the BMLD for a wider bandwidth. Their data support the hypothesis that these signal parameters are the reason for the contradicting results of Yasin & Henning () and van de Par & Kohlrausch (). They argued that the small BMLD for a short signal with short ramps embedded in a narrowband masker is due to spectral splatter that is off‐frequency information is used for signal detection.…”
Section: Band‐widening Experimentsmentioning
confidence: 99%
“…A similar problem also exists in patients who receive other hearing aids. Researchers think that a poor ability to localize sound in a complex auditory environment is responsible for the weak speech perception observed under these conditions[13]. Studies show that sound localization primarily depends on interaural time and intensity differences of sound signals[456].…”
Section: Introductionmentioning
confidence: 99%